2015
DOI: 10.1038/srep11111
|View full text |Cite
|
Sign up to set email alerts
|

Electric tuning of magnetization dynamics and electric field-induced negative magnetic permeability in nanoscale composite multiferroics

Abstract: Steering magnetism by electric fields upon interfacing ferromagnetic (FM) and ferroelectric (FE) materials to achieve an emergent multiferroic response bears a great potential for nano-scale devices with novel functionalities. FM/FE heterostructures allow, for instance, the electrical manipulation of magnetic anisotropy via interfacial magnetoelectric (ME) couplings. A charge-mediated ME effect is believed to be generally weak and active in only a few angstroms. Here we present an experimental evidence uncover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Such coupling mechanisms have indeed been reported theoretically and experimentally [20,21]. Performing large scale micro magnetic simulations for realistic material parameters we demonstrated how the features of the generated spin waves depend on a geometry of the stripe and the coupling at the interface.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Such coupling mechanisms have indeed been reported theoretically and experimentally [20,21]. Performing large scale micro magnetic simulations for realistic material parameters we demonstrated how the features of the generated spin waves depend on a geometry of the stripe and the coupling at the interface.…”
Section: Discussionmentioning
confidence: 84%
“…Generally, composite FE/FM are most interesting, as in these materials the interfacial magnetoelectric coupling turned out to be quite sizable even at room temperature, as evidenced by numerous studies [16][17][18]21]. Experimental verification and a direct observation of the ME coupling was reported recently for Co/BaTiO 3 -interfaces [19] and Co 92 Zr 8 /PMN-PT-films [20]. Several coupling mechanisms are discussed in the literatures.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, not only was a shift in the resonance field obtained, but an interesting change in the sign of the FMR lineshape was observed, which indicated that the excitations triggered by the electric field were transferred to the spin system via magnetoelectric coupling, as we previously reported. 23 As the temperature was increased, the shift in the resonance field increased and an obvious change in the sign of the lineshape occurred, which indicated the change of interface ME coupling in different temperature.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…9 and using compressive stress to stretch the Olsen cycle and enhance the pyroelectric effect. This aspect is in sofar interesting for future studies, as strain mediated ME coupling is indeed well-established, in addition to other coupling mechanisms [20][21][22][23][24][25][26][27][28][29] .…”
mentioning
confidence: 99%